2009
DOI: 10.1021/jp907497p
|View full text |Cite
|
Sign up to set email alerts
|

Surface Plasmon Raman Scattering Studies of Liquid Crystal Anchoring on Liquid-Crystal-Based Self-Assembled Monolayers

Abstract: We studied the anchoring of 6CB on a series of self-assembled monolayers (SAMs) with a functional group that mimics that of the nematic liquid crystal (LC). The SAMs were first characterized by wetting, Fourier-transform infrared spectroscopy, and surface potential measurements. We found that, in two of these SAMs, the end group dipoles were oriented close to the normal of the surface and that these promoted homeotropic anchoring. In the case of the other SAM, the dipole was oriented parallel to the surface, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 76 publications
1
13
0
Order By: Relevance
“…This strengthens the view that “alignment of Col h phases of DLCs is intrinsically homeotropic regardless of the nature of the DLC or the nature of the surface”: that the surface acts purely as a mechanical barrier, and although it is known that a specific interaction between the surface and the discogen can be used to enhance the ease or quality of the alignment, this factor seems to be of secondary importance. This is quite different to the situation which pertains in the case of calamitic liquid crystals where control of the surface chemistry, for example, control over the nature of a SAM surface or over the orientation within the “seed layer” provides a very simple way in which the alignment of the liquid crystal can be controlled. ,,,, …”
Section: Discussionmentioning
confidence: 89%
“…This strengthens the view that “alignment of Col h phases of DLCs is intrinsically homeotropic regardless of the nature of the DLC or the nature of the surface”: that the surface acts purely as a mechanical barrier, and although it is known that a specific interaction between the surface and the discogen can be used to enhance the ease or quality of the alignment, this factor seems to be of secondary importance. This is quite different to the situation which pertains in the case of calamitic liquid crystals where control of the surface chemistry, for example, control over the nature of a SAM surface or over the orientation within the “seed layer” provides a very simple way in which the alignment of the liquid crystal can be controlled. ,,,, …”
Section: Discussionmentioning
confidence: 89%
“…43,45,53 In the case of alignment layers treated with SAMs, different LC orientations have been observed using polar and nonpolar adsorbate molecules. 44,38,51 Additionally, chiral and "odd−even" 54 effects have been observed, showing that LC alignment is sensitive to variations in the symmetry 55−57 and orientation 46,47 of the exposed moieties of the terminal functionality of the SAM. Self-assembled adsorbates used in previous studies typically varied in two or more of these factors simultaneously (e.g., comparing structural analogues with different exposed moieties: −CH 3 , −OH, and −COOH).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Abbott and others have shown that SAMs also influence the alignment of LCs, with the ability to control both azimuthal and polar orientations, which have found use in sensors . However, a convolution of steric effects, surface topography, and intermolecular forces complicates our understanding of the mechanisms responsible for alignment. ,, Molecular adsorbates, in the form of either well-organized SAMs or adventitious surface contamination, can alter LC arrangement by changing the preferred in-plane alignment axis or inducing homeotropic alignment, normal to the surface. ,, In the case of alignment layers treated with SAMs, different LC orientations have been observed using polar and nonpolar adsorbate molecules. ,, Additionally, chiral and “odd–even” effects have been observed, showing that LC alignment is sensitive to variations in the symmetry and orientation , of the exposed moieties of the terminal functionality of the SAM. Self-assembled adsorbates used in previous studies typically varied in two or more of these factors simultaneously (e.g., comparing structural analogues with different exposed moieties: −CH 3 , −OH, and −COOH).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, reports of SERS in the KC have not focused on the understanding of the method, but mostly on its practical use in research as a characterization tool, for example to determine molecular orientations on the surface [113,114]. Such a move toward applications of the techniques further emphasize the need to complete our fundamental understanding of the underlying mechanisms.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…• Since all the cited studies but two [112,114] were carried out on Ag films, can this method be convincingly extended to Au films, which are a better alternative for applications, and are already extensively used in SPRS instruments.…”
Section: Historical Backgroundmentioning
confidence: 99%